Effect of Storage Duration on Physicochemical and Antibacterial Activities of Sweet Corn-based Synbiotic Yogurt with Honey - Musyirna Rahmah Nasution; Winda Sri Wahyuni (Chemistry Education Program, the University of Mataram, 2020)
Synbiotic yogurt is fermented milk containing probiotics and prebiotics. The quality of symbiotic yogurt products during cold storage must meet the SNI quality requirements (2981-2009). This study aimed to find the effect of yogurt storage duration on physicochemical properties and antibacterial activity for the best yogurt storage time. In this study, synbiotic yogurt was made from sweet corn, honey, and full cream milk as prebiotics and Lactobacillus acidophilus and Bifidobacterium bifidum as probiotics. The tests carried out include testing total coliform, total lactic acid bacteria, degree of acidity (pH), total titrated acid, organoleptic quality, and antibacterial activity. The tests were carried out on days 0, 5, 10, 15, and 20. The results showed that storage duration affected product quality and antibacterial activity. The best storage duration for yogurt was found to be ten days, where the yogurt stored for ten days found to have a total coliform of 0 APM/g, total lactic acid bacteria of 2.81 x 1012, total lactic acid of 1.684%, pH value of 3.5 and was still preferred and could be accepted by the panelists, based on the organoleptic assessments. The yogurt stored for ten days also gave the largest average inhibition diameter of 21.78 mm with the category 'very strong' against Escherichia coli and 22.13 mm with the classification 'very strong' against Salmonella typhi. The yogurt stored for up to 10 days still met the SNI yogurt quality standard requirements (2981: 2009).